In Situ Monitoring of Lipid Phase State Make Target Lipid Mixtures Similar to Intercellular Lipid in the Stratum Corneum. Issue 3 (16th January 2020) - Fujii, Mika Yoshimura; Gato, Katsuhiko; Ozawa, Yosuke; Hisada, Hiroshi; Koide, Tatsuo; Inoue, Motoki; Fukami, Toshiro
Abstract: In this study, lipid structural change is monitored using Raman spectroscopy during heat treatment, along with the impact of lipid states on the structural and physical properties during the preparation process of the dried and hydrated lipid mixture (LM) similar to intercellular lipid in stratum corneum. The microstructures and thermal behavior of these LMs change depending on the melting of lipid ingredients in the preparation process. It is recognized that variable temperature Raman spectroscopy (VT‐Raman) is a useful and attractive tool for the sensitive in situ monitoring of lipid state changes and lipid melting. The LMs can incorporate D2 O into their structures regardless of preparation temperature due to increasing lattice distance by hydration. These results suggest that monitoring lipid structural changes during the heating step is important to precisely prepare target LMs. Practical Applications : This study reveals that VT‐Raman is a useful and attractive tool in in situ monitoring of lipid state change and lipid melting. The monitoring of the preparation process by VT‐Raman is necessary to precisely prepare the target LM similar to intercellular lipid of stratum corneum because the microstructures and thermal properties of these LMs change depending on the melting of lipid ingredients during the preparation process. Abstract : In situ monitoring of lipid state change and lipid melting in preparation process of intercellular lipid model by variable temperature Raman spectroscopy and differential scanning calorimetry.